A limited contribution of Ca(2+) current facilitation to paired-pulse facilitation of transmitter release at the rat calyx of Held - Müller, Martin (Blackwell Science Inc, 2008)
Recent studies have suggested that transmitter release facilitation at synapses is largely mediated by presynaptic Ca(2+) current facilitation, but the exact contribution of Ca(2+) current facilitation has not been determined quantitatively. Here, we determine the contribution of Ca(2+) current facilitation, and of an increase in the residual free Ca(2+) concentration ([Ca(2+)](i)) in the nerve terminal, to paired-pulse facilitation of transmitter release at the calyx of Held. Under conditions of low release probability imposed by brief presynaptic voltage-clamp steps, transmitter release facilitation at short interstimulus intervals (4 ms) was 227 ± 31% of control, Ca(2+) current facilitation was 113 ± 4% of control, and the peak residual [Ca(2+)](i) was 252 ± 18 nm over baseline. By inferring the ‘local’[Ca(2+)](i) transients that drive transmitter release during these voltage-clamp stimuli with the help of a kinetic release model, we estimate that Ca(2+) current facilitation contributes to ∼40% to paired-pulse facilitation of transmitter release. The remaining component of facilitation strongly depends on the build-up, and on the decay of the residual free [Ca(2+)](i), but cannot be explained by linear summation of the residual free [Ca(2+)](i), and the back-calculated ‘local’[Ca(2+)](i) signal, which only accounts for ∼10% of the total release facilitation. Further voltage-clamp experiments designed to compensate for Ca(2+) current facilitation demonstrated that about half of the observed transmitter release facilitation remains in the absence of Ca(2+) current facilitation. Our results indicate that paired-pulse facilitation of transmitter release at the calyx of Held is driven by at least two distinct mechanisms: Ca(2+) current facilitation, and a mechanism independent of Ca(2+) current facilitation that closely tracks the time course of residual free [Ca(2+)](i).